New Zealand's strategic interests in Antarctica - Brady, Anne-Marie (Polar Record, 2010)
ABSTRACT New Zealand has important strategic interests in Antarctica that are as much about geography and the country's geostrategic needs, as they are about history and the politics of maintaining rights gained in an earlier era. This paper outlines the reasons behind New Zealand's involvement in and commitment to Antarctica; profiles the various bodies involved in maintaining and negotiating New Zealand's Antarctic presence and voice on Antarctic affairs; and discusses New Zealand's core interests in the Antarctic continent that help to shape its Antarctic policy.